Two control systems modulate the level of glutaminyl-tRNA synthetase in Escherichia coli. - Cheung, A Y (1985)
We studied the regulation of in vivo expression of Escherichia coli glutaminyl-tRNA synthetase at the transcriptional and translational level by analysis of glnS mRNA and glutaminyl-tRNA synthetase levels under a variety of growth conditions. In addition, strains carrying fusions of the beta-galactosidase structural gene and the glnS promoter were constructed and subsequently used for glnS regulatory studies. The level of glutaminyl-tRNA synthetase increases with the increasing growth rate, with a concomitant though much larger increase in glnS mRNA levels. Thus, transcriptional control appears to mediate metabolic regulation. It is known that glnR5, a regulatory mutation unlinked to glnS, causes overproduction of glutaminyl-tRNA synthetase. Here we showed that the glnR5 product enhances transcription of glnS 10- to 15-fold. The glnR5 mutation does not affect metabolic control. Thus, glnS appears to be regulated by two different control systems affecting transcription. Furthermore, our results suggest post-transcriptional regulation of glutaminyl-tRNA synthetase.